O ensino de enfermagem gerontológica na formação do enfermeiro - Lima, Heloisa Cristina Ferreira de (2014)
At the current time of demographic changes in the world , it is observed that the health sector requires restructuring of its practices in caring for the elderly , in order to enable a comprehensive and humane care . In this sense, we identify the need for qualified professionals to assist the elderly and, therefore , it is important that training curricula are adequate to this reality . The study aims to analyze how it develops teaching gerontological nursing component in undergraduate nursing . This is a descriptive , exploratory study with a qualitative approach, in two higher education institutions in the city of Natal / RN . The population involved corresponded to the coordinators of graduate courses in nursing and teachers who teach content of health care for the elderly, a total of seven participants . The data collection instruments were used: a questionnaire containing questions related to the characterization of the participants and the teaching of gerontological nursing in undergraduate courses in nursing and a form with items of analysis for pedagogical projects . The results were presented descriptively in tables and analyzed from coming themes of the main themes of the instruments defined in: knowledge about the research participants , knowledge of teaching gerontological nursing component and knowledge of pedagogical projects , discussed under Resolution paragraph . 03 of 7/11/2001 , which establishes standards for the nursing program , the educational projects of educational institutions , the Theoretical Donald Shoon and thematically relevant literature . The results indicate that the majority of participants were female (four), all have graduate though , none of them stated in the qualification of aging or elderly health area; the organization of the contents of the component in the curriculum, workload theoretical- methodological and practical teaching strategies presented was heterogeneous and sometimes diverging at the same institution . On the definition of gerontological nursing component was identified that is not well defined along the pedagogical design of educational institutions surveyed . It was concluded that in the context of this study , teaching gerontological nursing is present in the course of nursing education, but needs reevaluation and updating in order to teach a wider range of driving and health practices